The aesthetic dimension of nature. Research perspectives - Anna Marta Żukowska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The article concerns the aesthetic dimension of nature and its influence on the human. The author explains the notion of "nature," characterizes attitudes adopted towards it, and demonstrates the range of influence the natural environment has on the human. subsequently, the text focuses on the aesthetic perception of nature. in the light of the presented reflections, it outlines research perspectives concerning the influence of the relationship between humans and the natural environment on the aesthetic perception of nature.